MODELOS DE FORMAÇÃO CONTINUADA DE PROFESSORES: transitando entre o tradicional e o inovador nos macrocampos das práticas formativas - Janaína da Silva Ferreira; José Henrique dos Santos (Universidade Federal do Maranhão, 2016)
: This article aims to understand the structure of continuing education teachers, from the analysis of different concepts that govern and guide the practices in this area. Through a Critical Review of the Literature, opinionated type, we see the existence of different structural models, greatly influencing the teaching, learning and teacher training. The models differ in relation to the concepts, objectives and methodologies which are developed from different interests and, in turn, shape the nature of teaching learning. With the description of these perspectives, we seek to relate them to the reality of the practices adopted and developed by education systems and schools. Knowledge of these models becomes essential to reflect on the association of training practices to the needs of institutions, teachers and professional development. Training proposals guided by the teachers' needs will be more effective because their attention and efforts will turn to articulate the theory and practice to solve teaching and learning problems, reflecting the improvement of the quality of the educational process and, consequently, of all the educational system.